PENGARUH TARIF, JAM KERJA DAN JUMLAH BONUS TERHADAP PENDAPATAN DRIVER MAXIM DI KOTA RANTAUPRAPAT (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of fares, working hours, and bonus incentives on the income of Maxim online transportation drivers in Rantauprapat City. This research employs a quantitative approach using a survey method. The population consists of all active Maxim drivers in Rantauprapat City, with a sample of 85 respondents selected using a random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics. The results show that partially, fares, working hours, and bonuses have a positive and significant effect on the income of Maxim drivers. Simultaneously, these three variables also have a significant effect on drivers’ income. The coefficient of determination indicates that 64.2% of the variation in driver income can be explained by the variables of fares, working hours, and bonuses, while the remaining percentage is influenced by other factors not examined in this study. Therefore, reasonable fare policies, optimal working hours, and attractive bonus incentives can contribute to increasing the income of Maxim drivers in Rantauprapat City.